TASKS OF CITRUS BREEDING SCIENCE IN UZBEKISTAN (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
In the climatic conditions of Uzbekistan, the limonaria greenhouse of the Kibray District of the Tashkent region is under laboratory conditions.Based on the methods used by Z.Fakhruddinov's selection work, new native plant varieties of lemons were prepared, adapted to climatic conditions, as well as developed improved styles and created new varieties of high-yielding, stress-resistant, citrus plants, hybridization with local varieties, by welding and artificial cross-dressing, it was possible to select shapes and create on their basis competitive new varieties that are resistant to disease, rich in fertile sweet vitamins.
Keywords: Citrus, plant, varieties, climate, greenhouse laboratory, disease, sehosility, cultural varieties, durable